A profile of the elderly admitted to the emergency unit of Groote Schuur Hospital : with particular reference to their health care needs - Schuurmans-Stekhoven, Penelope M (Division of Geriatric Medicine, 2018)
This study is the first of its kind undertaken at Groote Schuur Hospital. It is an attempt to provide a holistic profile of their elderly patients with a view to encouraging further, more specific research, and to provide information for use in the planning of efficient health care for the aged. The study was based on three premises: (i) there is an interrelationship between the ageing process and disease; (ii) a non-disease-specific approach which focusses on the functional status of elderly patients can be used as a predictor of health services consumption; and (iii) any study which promotes understanding of the dynamics of health care of the elderly must also take into account the ageing process and its effect on a particular population within a specific social context. The research spanned 52 weeks (1 March 1989 - 27 February 1990). A sample of nine patients per week was selected from the total population of patients aged 65 and over admitted to the Emergency Unit of Groote Schuur Hospital. Two adult female researchers, using structured questionnaires, constructed in English and comprising subtests, utilising indexes and scales, interviewed respondents and/or household members in their own homes. Data was also obtained from the hospital files. Although essentially descriptive by nature, use was made of groups in regard to variables such as "first admission" (admission to the Emergency Unit), and "readmission" (a previous overnight admission in the preceding year). Statistical analysis, where indicated, was by means of non-parametric tests.